SOA-dependent N400 and P300 semantic priming effects using pseudoword primes and a delayed lexical decision - Hill, Holger; Remmen, Friederike Christina; Weisbrod, Matthias (International journal of psychophysiology, 2005)
In a previous semantic priming study, we found a semantic distance effect on the lexical-decision-related P300 when SOA was short (150 ms) only, but no different RT and N400 priming effects between short and long (700 ms) SOAs. To investigate this further, we separated priming from lexical decision, using a delayed lexical decision in the present study. In the short SOA only, primed targets evoked an early peaking (∼480 ms) P300-like component, probably because the subject detected the semantic relationship implicitly. We hypothesize that in tasks requiring an immediate lexical decision, this early P300 and the later lexical decision P300 (∼600 ms) are additive. Secondly, we found both a direct and an indirect priming effect for both SOAs for the ERP amplitude of the N400 time window. However the N400 component itself was considerably larger in the long SOA than in the short SOA. We interpreted this finding as an ERP correlate for deeper semantic processing in the long SOA, due to increased attention that was provoked by the use of pseudoword primes. In contrast, in the short SOA, subjects might have used a shallowed semantic processing. N400, P300, and RTs are sensitive to semantic priming—but the modulation patterns are not consistent. This raises the question as to which variable reflects an immediate physiological correlate of semantic priming, and which variable reflects co-occurring processes associated with semantic priming.
Gesehen am 22.12.2021